2022
DOI: 10.1097/md.0000000000030696
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative delirium in elderly urological patients: A meta-analysis

Abstract: Background: Avoiding postoperative delirium (POD) can have a significant detrimental effect on the rehabilitation and prognosis of elderly urological patients. It is necessary to explore the risk factors associated with POD in elderly urology to provide a basis for clinical recognition of delirium.Methods: For relevant studies, we comprehensively searched Embase, MEDLINE, Ovid, PubMed, Scopus, The Cochrane Library, and Web of Science. The search deadline was September 2021.Results: We identified 2046 studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Compared with a previous meta-analysis [ 6 ], our systematic review and meta-analysis included articles that were published within the latest 5 years and that summarized the incidence of POD after head and neck cancer surgery. The prevalence of POD varies significantly among surgical populations; for instance, the incidence of POD is reportedly 5.45 to 28.57% after urological surgery, 10.09 to 51.28% after hip fracture surgery, and 4.1 to 54.9% after cardiac surgery [ 13 , 14 , 32 ]. In our study, the incidence of POD ranged from 4.2 to 36.9% with a pooled incidence of 20% and high heterogeneity (I2 = 93.2%, P < 0.001), which was consistent with a previous meta-analysis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with a previous meta-analysis [ 6 ], our systematic review and meta-analysis included articles that were published within the latest 5 years and that summarized the incidence of POD after head and neck cancer surgery. The prevalence of POD varies significantly among surgical populations; for instance, the incidence of POD is reportedly 5.45 to 28.57% after urological surgery, 10.09 to 51.28% after hip fracture surgery, and 4.1 to 54.9% after cardiac surgery [ 13 , 14 , 32 ]. In our study, the incidence of POD ranged from 4.2 to 36.9% with a pooled incidence of 20% and high heterogeneity (I2 = 93.2%, P < 0.001), which was consistent with a previous meta-analysis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delirium is a ubiquitous complication in the postoperative period [56,57]. Studies have shown that elderly hospitalized patients with hip fractures are more likely to develop delirium resulting in increased mortality [58].…”
Section: Prognosis and Complicationsmentioning
confidence: 99%
“…Cognitive impairment was present in 53.8% of postoperative delirium (POD) patients compared Open Access Journal of Neurology & Neurosurgery to 4.4% of those without delirium [60]. Other delirium-related complications include aspiration pneumonia, falls, restraint use, pressure ulcers, readmissions, hospital-acquired comorbidities, increased hospital length of stay resulting in higher morbidity and mortality, higher healthcare cost, and increased financial burden to the family and society [56,57,59,61,62]. Delirium is also a risk factor for frailty due to increased morbidities seen in delirious patients [55,58,59,63].…”
Section: Prognosis and Complicationsmentioning
confidence: 99%